Prototype expert system for material selection of polymeric composite automotive dashboard - Salit, Mohd Sapuan; Mun, N. K.; Arep @ Ariff, Hambali; Lok, H. Y.; Abd Manab, Mohd Fairuz; Ishak, Mohamad Ridzwan (Academic Journals, 2011)
As a consequence of rapid development in material technology, determination of the right material for a given engineering application was viewed as a crucial decision. Various polymer materials selection methods have been developed to assist designers to determine the right polymer for a given engineering application. This paper presents a new natural fibre composite material selection process for automotive dashboard using expert system. The software tool chosen to assist the development of this expert system is PHPMyAdmin. The software tool was written in Hypertext Preprocessor (PHP) language designed to handle the administration of My Structure Query Language (MySQL) server over the World Wide Web. Various polymer composite properties are considered in order to develop the system. The focused properties of composites in this study are the density, Young’s modulus and tensile strength. In order to demonstrate the system implementation, a car dashboard has been selected as a case study. It has been shown that using PHPMyAdmin for polymer composite materials process can assist designers to determine the right polymer composites for a given engineering application.